Вы находитесь на странице: 1из 18

1) -

:A.B.., -a,b . a
A, a A.
:
I): {x:(X A)V(x B)}
II): {x:(x A)/\(x B)}
III):{x:(x A)/\(x B)}
IV) A: {x:(x A)
V) : AB:{x:((x A)/\(x B))V(x A)/\(x B)
VI) : A*B- ,
.
{(ab):a A,b B)}
,
. y=z^2
, . E
, .
1<=n<=N, N- .
- ,
.
.
.

.
A={a1,a2....an}
B={b1,b2...bn}
AVB={a1....an,b1,b2....bn}

.
aVBVC={a1,b1,c1,a2...}

, .
.
, , <=.
B, ,
B.
13)
I) .
II) .
III) .
IV) .
V) .
VI) .
VII) .
VIII) .
:, .

http://www.matburo.ru/Examples/Files/
Issled7.p

10) - ,

. ,

.

f(x) g(x) a,
, , a,

. ,


x,

, f(x)/g(x)
(1)

0/0



, - .

9). . g(x) [a,b],


g(a)=g(b)=0,
a < c < b g
g(c)=0.
. [a,b],
(M) m. g(c) - .

g(c+Dx) - g(c)

0, Dx > 0

Dx

g(c+Dx) - g(c)

0, Dx < 0

Dx

. . g(x) [a,b],
, a < c
< b
g(b)-g(a)=g`(c)(b-a)
.
g(x)-g(a)-(x-a)Q,

Q=(g(b)-g(a))/(b-a).
. . g(x) h(x) [a,b],
, h(x) 0 [a,b],
a < c < b

7) f .
f
f". ,
f"(x) = (f'(x))'.
(n - 1)- f, n-
(n - 1)- f f(n). ,
f(n)(x) = (f(n-1)(x))', n N, f(0)(x) = f(x).
n .
n- f
(n - 1)- . ,
dnf(x) = d(dn-1f(x)), d0f(x) = f(x), n N.
x - ,
dx = const d2x = d3x = ... = dnx = 0.

dnf(x) = f(n)(x)(dx)n.


u v - n- ,

6) =()

,
, d ( d()):
dy='(). (24.1)
d .

.
dy/dx='().
dy/dx dy d.
.

=() (; )
+. =, |
AM1|=. :

(24.1), dy=, . .
=()
,
.

5) f x0
x, x0,
f(x) f(x0) x x0,
.
x ,
x0. x x0 (
) x0 x. ,
x = x x0,
,
x = x0 + x.
, x0 x.
f
f(x) f(x0) = f (x0 +x) f(x0).
f x0,
x, f ( ), ..

f = f (x0 + x) f (x0),

f (x) = f (x0 +x) = f (x0) + f.


x0 f x. f
y y = f(x).


,
:

y = f() = x
(, f(x)), . .

x(t),


x , ,
, ,
.
:
x
, ,
.
f(x) 0,

f = f(x0 + x) f(x0) = A x + o(x) ,
A , , o(x)
x 0 .
, f(x) x0,
, .
. , , .
. dx
x, ..
dx x.

u=u(x) v=v(x) x , (),


,
:

.

.

x,

y.

= f(x) M (x1 ; y1) .

( ).
, k y = f(x) M (x1 ;
y1) f '(x1) y' = f '(x) x = x1/ ,
,
, ..

y - y1 = f '(x1)(x - x1)
,

2) y = f(x), x N, N
( ), y = f(n) y1, y2,, yn,. y1, y2,
y3, , , , .

, .
.

, ,
. .


(
) , , .

,
.

N ,

.
.

. , .

, ,
.

{xn} ,
a, N() ,
n>N xn xna<

.
.
{xn} {yn}
, {xn} {yn}.
{xn} {yn}
, {xn} {yn}
{xn} {yn}
, {xn}
{yn}.
{xn} {yn},
, , ,
, {xn} {yn}.

{n}, {n} {zn}.


15.1.

, , n n ab.
,
.

,
, .

.
.
.

.
,
.

.

.

e , , .

e :

2,718281828...

3) , ,
,
.
, <0
, , , , (-)
<E, F(x)-<E.
f(x) a , > 0 =
() >0,
|f(x' ) - f(x" )| < ,
0 < |x' - a| < 0 < |x' - a| < , x' x" - f(x).

, ..

,
;

,
, ..

.
,

- .

=,
, ->.

,
.

f(x) xa, 1/f(x)


xa.
f(x) - xa ( x) , y=1/
f(x) .
, ,
, .
2. f(x) g() . f(x)
g{x), f(x)g(x) f(x)/g(x) ( 0) , ,
/.
3. f(x), g(x) h(x)
, , , f(x) g(),
, :
f(x) h(x) g(x).

\\

8) y f x = ( ) F x y ( , ) = 0 . ,
.

y'(x)
:

x, ,
y - x
;

y'(x).


f
x = (t), y = (t), < t < ,
y = f(x) , '(t) 0,

12) ()


,
.
.

. ,
.

, ,

, , .
f(x) (a,b),
x f(x)
, ..
f(x2) > f(x1) x2 > x1.
,
, .
,
.
. x0 f(x), h
>0, :
f(x 0-h )>f (x 0) f(x 0+ h)>f(x 0),
. , x

f ( x ) > f ( x 0 ).
. x0 f(x), h
>0, :
f(x 0-h)< f(x 0) f(x 0+h )< f(x 0),
. , x
:
f ( x ) < f ( x 0 ).

. , f(x) (a,b)
(), (a,b) (. 1,2) (
) .

:
,
(. 10.11).

. 10.11
, , , . :
( ..)
: f(x),

,
,
.
:

,
.

,
, .
, :
.
7.1


- :

,
,

7.2

1)

, :

2) 0

:
(7.1)

1)

2) 0

4)
F(x) 0, :
1) 0
2) Limf(x)
3)limf(x)=f9x0)
0 ,
, 0 .
:
0, :

-. f(x) [a,b]
.
[,b] f(c)=0.
-. f(x) <a,b>
.

m<C<M

<a,b> f(c)=C.

( )
, .
: , [a;b]
. (xn) xnk,
x0[a;b] .
f [a;b], , , nN
xn[a;b] , f(xn)>n. n 1,2,3,{\ldots},
(xn) [a;b], f(x1)>1,f(x2)>2,f(x3)

>3,...,f(xn)>n...
(xn)
(xnk), x0[a;b] : limkxnk=x0 (1)
(f(xnk)). f(xnk)>nk
limkf(xnk)=+ (2),
, (1)
limkf(xnk)=f(x0) (3)
(2) (3) ( ).
. .
...

: f(x) [a,b],
, ,
, .
:
f(x) [a,b], 1 .
, .
.

:
[a,b]:
,

f(x)
.
.